A narrative review and future considerations of spinal cord stimulation, dorsal root ganglion stimulation and peripheral nerve stimulation. Issue 6 (December 2021) - Malinowski, Mark N.; Chopra, Pooja R.; Tieppo Francio, Vinicius; Budwany, Ryan; Deer, Timothy Ray
Abstract : Purpose of review: In recent years, neuromodulation has experienced a renaissance. Novel waveforms and anatomic targets show potential improvements in therapy that may signify substantial benefits. New innovations in peripheral nerve stimulation and dorsal root ganglion stimulation have shown prospective evidence and sustainability of results. Sub-perception physiologic bursting, high-frequency stimulation and feedback loop mechanisms provide significant benefits over traditional tonic spinal cords stimulation (SCS) in peer reviewed investigations. We reviewed the themes associated with novel technology in the context of historical stalwart publications. Recent findings: New innovations have led to better nerve targeting, improvements in disease-based treatment, and opioid alternatives for those in chronic pain. In addition, new neural targets from both structural and cellular perspectives have changed the field of Neurostimulation. Summary: For many years, tonic SCS was representative of neuromodulation, but as this review examines, the progression of the field in the past decade has reshaped patient options.